Strengthening Digital-Based Inner Child Intervention in Demak's Integrated Islamic Elementary Schools - Zuhri, Zuhri; Anh, Nguyen Thi Lan; Munir, Muhamad Misbahul (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
This study aims to describe and apply E-attendance and E-money in education at SDIT in Demak, as well as to encourage students to have high discipline and be economical in using school funds, with parents only allowed to transfer a limited amount each day. This study uses a descriptive qualitative method. The study examines the phenomenon of students using E-attendance and E-money. The research subjects consist of first-grade students and their parents. Data collection techniques include observation, interviews, and documentation. The research findings indicate that digitalization in education has received positive feedback from the outset through guidance from teachers and training, enabling students to effectively and efficiently apply digitalization at school. This allows parents to monitor their children's academic progress and learning quality at school, as well as manage their finances efficiently when purchasing snacks at school. Meanwhile, the positive impact of educational digitalization for children is that they can utilize technology for education, while parents who are busy at home or at work can enjoy administrative and financial comfort and security. The novelty found is that technology has become a necessity in life from an early age to old age, to fulfill the process of life at the national and global levels.